A Comparative Study on the Origin and Variety of Motifs in Shahsavan Salt Bags and Caucasian Textiles - Egharloo, Siamak; Abozari, Hadi; Afshar, Mahdi Keshavarz (Journal of History Culture and Art Research, 2017)
Shahsavan tribes of Iran and the Caucasus region have had considerable and often inevitable intercourse and associations during the history due to their common borders and special geographical locations. The result of this has been manifested in different forms of intermingled factors and elements, specifically the textiles of tribes and ethnic groups. The interactions of the mentioned realm, i.e. textile industry, have best been appeared in patterns, motifs, colors and compositions and weaving of the hand-woven textiles among which Shahsavan "salt bags" (NAMAKDᾹN) are a case in point. According to the facts and the importance of this subject, we can propose some questions as follows: What influences have the field of weaving had in these two regions as a result of their interactions and historical background? What are the motifs and their classifications in these two regions and which ones share common patterns? And which ones abound? Having been done in analytical and comparative method, the present research has examined the field of weaving in Shahsavan tribe with emphasis on its salt bags together with other Caucasian textiles (salt bags, etc.). The objectives of the research have been the study of the influences and interactions between the two regions and the recognition of patterns and motifs on their textiles. Finally, we can infer that the certain location of Iran and its common borders with the Caucasus besides tribal distribution of groups in northern and southern areas could be considered the reasons for cultural influences in the mentioned regions. The dominant motifs to be noticed here are dragons (S shape), diamonds and stars, crab-like and cross motifs as well as negative and positive spaces.